2000
DOI: 10.1097/00000658-200007000-00017
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Study on Bilateral Carotid Endarterectomy: Patching Versus Eversion

Abstract: ObjectiveTo compare the clinical outcome and restenosis incidence of patients who underwent carotid endarterectomy with patch closure (CEAP) on one side and carotid eversion endarterectomy (CEE) on the other. Summary Background DataAlthough a few investigators have compared the results of CEAP versus CEE, no reports have compared the outcome of CEAP versus CEE in the same patient. MethodsEighty-six patients were randomly selected for sequential surgical treatment involving either CEAP/CEE or CEE/CEAP. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 37 publications
2
77
0
1
Order By: Relevance
“…In the series reported by Shah et al, 75 the rates of restenosis were close to 4 times less frequent (0.3% in the eversion CE group, and 1.1% in the conventional CE group). In a randomized trial, Ballotta et al 6 showed no late restenosis in a group of patients who had undergone eversion, compared with 4.7% in their patched group. The pooled results from randomized trials comparing eversion with conventional treatments showed a statistically significant reduction in the incidence of delayed restenosis with eversion CE.…”
Section: Hemodynamic Consequences and Restenosismentioning
confidence: 95%
“…In the series reported by Shah et al, 75 the rates of restenosis were close to 4 times less frequent (0.3% in the eversion CE group, and 1.1% in the conventional CE group). In a randomized trial, Ballotta et al 6 showed no late restenosis in a group of patients who had undergone eversion, compared with 4.7% in their patched group. The pooled results from randomized trials comparing eversion with conventional treatments showed a statistically significant reduction in the incidence of delayed restenosis with eversion CE.…”
Section: Hemodynamic Consequences and Restenosismentioning
confidence: 95%
“…Numerous studies have compared standard CEA plus patching with eversion once [7][8][9][10][11][12][13][14][15][16][17][18]. Regarding the total operating and ischemic time, as well as perioperative complications, first studies has favored to eversion CEA [7,8].…”
Section: Reviewmentioning
confidence: 99%
“…Namely, on the one carotid artery at the same patient, Balotta and associates performed eversion, while on another side conventional CEA [9]. Regarding early and long term results, eversion CEA has been better [10].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Published studies, whether from randomized [15][16][17][18][19] or singlearm trials, have included patients with symptomatic as well as asymptomatic carotid disease. 20 -24 By contrast, the Stent-Protected Angioplasty versus Carotid Endarterectomy (SPACE-1) study included only symptomatic patients, randomized to carotid artery stenting or CEA with a conventional or eversion technique.…”
mentioning
confidence: 99%